Pharmacokinetics and pharmacodynamics of antibiotics in central nervous system infections. Issue 1 (February 2018) - Nau, Roland; Seele, Jana; Djukic, Marija; Eiffert, Helmut
Abstract : Purpose of review: The barriers surrounding the central nervous system (CNS) together with the emergence of multiresistant pathogens pose a therapeutic challenge for the effective treatment of CNS infections. Recent findings: In addition to vancomycin, colistin and aminoglycosides, classically used for intrathecal injection, drug concentrations in cerebrospinal fluid after intrathecal injection of daptomycin and tigecyclin were recently studied. Summary: The entry of antiinfectives into the CNS compartments is determined by the physicochemical properties of the drug and by conditions in the host. The most important drug properties are lipophilicity at a neutral pH, molecular mass and drug binding to serum proteins. In clinical practice, active transport is of importance only for some drugs. In recent years, intrathecal injection of antiinfectives in addition to systemic therapy has regained attention as a means to achieve high cerebrospinal fluid concentrations. The classification of antibacterials and antifungals into time-dependent and concentration-dependent compounds is also valid for the CNS compartments.